Shared Shrines and the Discourse of Clashing Civilisations - Bowman, Glenn ca. 20./21. Jh. (Entangled Religions, 2019)
Since I began, in the early 1980s, to research Muslim-Christian cohabitation of religious sites, I have been convinced of the political importance of making practices of intercommunal 'sharing' ethnographically visible. Thirty-five years of that work, spread across the Eastern Mediterranean (Israel/Palestine, Yugoslavia and its successor states, and both sides of the Cyprus divide), have not only revealed contemporary and historical choreographies of cohabitation but also their disintegration and the forces which bring it about. While I was carrying out this research, an accelerating resurgence of ethnic, religious and nationalistic politics was taking place not only throughout the areas I was studying but also in the global arena. This 'identitarian' politics, its philosophical grounding, and its shaping of academic and popular thought and practice is the focus of the first half of this paper; in the second part I look theoretically and empirically into examples of sharing and its refusal so as to show not only how cohabitation with alterity works but also to make visible the processes which sabotage it.